Adventures of an export salesman: travel, race, and sex abroad in a 1970s Finnish pornographic magazine. Issue 1 (2nd January 2017) - Saarenmaa, Laura
ABSTRACT: During the 1970s, pornographic magazines that envisioned the Finnish man sovereignly enjoying sexual pleasures in Eastern Europe, the Soviet Union, the Middle East, and the Far East became extremely popular in Finland. In this article it is argued that pornographic magazines functioned as geographical as well as sexual maps; through the medium of magazines, Finnish readers were educated to think of themselves as privileged, 'white', 'Western European' men. The article addresses the topic of racial pornographies by drawing on the geopolitical conditions of the construction of Finnishness as western whiteness in the travel narratives of Kalle magazine between 1973 and 1977. In addition to racial differences, the article examines the Cold War conditions of the 1970s as a major contributor to the Nordic colonial mind, here referring to a generalized identification with colonial exploitation.